DEVELOPING ENGLISH LANGUAGE SKILLS THROUGH CRITICAL THINKING IN HIGHER EDUCATION - Abdirakhimova Mokhigul Normurodovna; Akhrorov Saidamin Sayfutdinovich; Mamadyokubova Ismigul Ural kizi; Jabborov Asilbek Jamshid ogli (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Annotation: This article explores the role of critical thinking in teaching English in higher education. In modern education, developing students’ ability to analyze, evaluate, and interpret information is as important as acquiring language skills. The study examines how integrating critical thinking activities into English language instruction enhances learners’ communicative competence and cognitive development. Particular attention is given to interactive methods such as debates, problem-solving tasks, and analytical writing. The findings suggest that critical thinking-based instruction significantly improves students’ engagement, autonomy, and overall language proficiency.